APPLICATION OF E-GOVQUAL AND IMPORTANCE-PERFORMANCE ANALYSIS (IPA) METHODS TO EVALUATE E-FILING SERVICES: A CASE STUDY OF WP OPs IN JABODETABEK - Aulia; Caecilia Widi Pratiwi; Sulistining Trimulyani (Akuntansi research UGR, 2024)
E-filing is a way of electronically submitting an Annual Tax Return, done online and in real-time via the Internet on the DJP website. This study aimed to determine the effect and evaluate the quality of e-filing applications in public services so that in the future, it can improve public services to the community. The object of this research is 120 WP OPs in Jabodetabek. This study uses the e-GovQual method to determine the attributes of the research questionnaire. The variables used are efficiency, trust, reliability, and citizen support. The sampling technique is purposive sampling. The analysis tools used are validity test, reliability test, path coefficient, and importance performance analysis (IPA). IPA is used to calculate data from the questionnaire and find out which attributes need improvement. Based on the results of the research that has been done, efficiency and citizen support affect user satisfaction. Meanwhile, trust and reliability do not affect user satisfaction. The average value of the conformity level is 100.61%, indicating that the service performance has met user expectations. The gap value is 0.03%, meaning that the performance and service have met user expectations. Two attributes need to get top priority for improvement: the information displayed on the e-filing application is the latest information (EF6), and the e-filing application runs well when using the browser on my computer/laptop/gadget (RB5).